Solving Fuzzy Game Problem in Octagonal NEUTROSOPHIC Numbers Using Heavy OWA Operator - Selvakumari, K.; Lavanya, S. (International Journal of Engineering and Technology, 2018)
In this paper, we define octagonal neutrosophic number (ONN) and operations on it. Also, we define -cut sets of ONN. We use octagonal neutrosophic numbers as pay offs of two- person zero sum game and propose a new method to find the best strategies for the two players using heavy ordered weighted averaging (HOWA) operator on these numbers. The applicability of this method is explained through a numerical exampleÂ